Participation of epidemiologists and/or biostatisticians and methodological quality of published controlled clinical trials. Issue 8 (1st August 2001) - Delgado-Rodriguez, M; Ruiz-Canela, M; De Irala-Estevez, J; Llorca, J; Martinez-Gonzalez, M A
Abstract : STUDY OBJECTIVE: This study assessed several methodological aspects related to the quality of published controlled clinical trials (CCTs) in relation to the participation of an epidemiologist/biostatistician (E/B). DESIGN: Handsearch of CCTs published in four medical leading journals for 1993–1995. METHODS: Quality variables, abstracted from a review, were related to authors' specialties. Five hundred and ninety four CCTs were identified via a hand search. The department/unit membership was used to attribute authors' specialties. Of 594 CCTs identified, in 127 the authors' specialties could not be known, leaving 467 trials for analysis. RESULTS: E/B participation occurred in 178 trials (38.1%). This participation was more frequent in multicentric, bigger, and in those trials describing any funding agency. These factors were controlled for in the analysis. E/B participation was positively associated with pre-study sample size estimation (OR = 1.5, 95% confidence intervals (CI) 1.0, 2.3), with reporting the dates for starting/ending the study (OR = 2.1, 95% CI 1.4, 3.3), with using an objectively assessed outcome (OR = 2.4, 95% CI 1.2, 4.6) and with the intention to treat principle (OR = 2.0, 95% CI 1.3, 3.0). The overall quality score was higher in trials where E/B participated. CONCLUSIONS: The results suggest that E/B improve the quality (at least of reports) of clinical trials. Given that quality of research is frequently used to evaluate potential sources of heterogeneity between trials, these results are relevant for meta-analysis.